'Mental health is what makes life worth living': an exploration of lay people's understandings of mental health in Denmark. Issue 1 (1st January 2017) - Nielsen, Line; Sørensen, Betina Bang; Donovan, Robert J.; Tjørnhøj-Thomsen, Tine; Koushede, Vibeke
Abstract: How people understand mental health has important implications for designing and implementing mental health promotion, and particularly where campaigns developed in one culture are implemented in another. Hence, as part of an adaptation of the Australian Act-Belong-Commit mental health promotion campaign into the Danish context, this qualitative study explored Danish lay people's understandings of mental health and mental health promoting factors. In total, N  = 39 individuals (27 adults and 12 young people) from various regions across Denmark participated in seven focus groups interviews. Two overall and intertwined understandings of mental health emerged: mental health as a 'state of mind' and mental health as a relation. Overall, Danish people's understanding of what constitutes good mental health and what people can do to keep mentally healthy were consistent with the underlying messages in the Act-Belong-Commit campaign, and hence translatable to a Danish context. Given the lack of research in the area, this study contributes to the literature on lay people's understanding of concepts around mental health and keeping mentally healthy.